ANALYSIS OF STUDENT DISCIPLINE IN THE LEARNING PROCESS DURING THE COVID 19 PANDEMIC; CASE STUDY CLASS V SDN 1 POSONA - Surahman Wilade; Sisriawan Lapasere; Wahyuni Wahyuni (Jurnal Dikdas, 2022)
The purpose of this study was to determine the teacher's role in fostering student discipline at SDN 1 Posona, to determine the inhibiting factors in fostering student discipline at SDN 1 Posona. This study uses a qualitative descriptive research model. The research subjects were 20 students. The data collection techniques used were interviews, questionnaires, observation and documentation. In fostering student discipline, namely, using an exemplary approach and getting used to discipline, religious, independent, responsible, fond of reading and caring for the environment. The inhibiting factors for the teacher's role in fostering student discipline are: The corona disease outbreak, the influence of peer relationships in the student's residential environment, limited communication between students' parents and students due to economic factors and being too busy with personal gadgets. And the results of the study show that: the teacher's role in fostering student discipline at SDN 1 Posona in online learning from a total of 20 student respondents which can be seen from the percentage can be concluded in the very high category.